2021
DOI: 10.5713/ajas.20.0325
|View full text |Cite
|
Sign up to set email alerts
|

ssc-miR-185 targets cell division cycle 42 and promotes the proliferation of intestinal porcine epithelial cell

Abstract: Objective: microRNAs (miRNAs) can play a role in a variety of physiological and pathological regulation, and its role is achieved by regulating the expression of target genes. Our previous high-throughput sequencing found that ssc-miR-185 plays an important regulatory role in piglet diarrhea, but its specific target genes and functions in intestinal porcine epithelial cell (IPEC-J2) are still unclear. We intended to verify the target relationship between porcine miR-185 and cell division cycle 42 (CDC42) gene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Subsequently, 10 miRNAs were selected to construct the circRNA-miRNA interaction network (Fig. 4 c), among which 5 were targeted miRNAs of the key candidate circRNA found in this study, and the other 5 selected miRNAs were found to be related to bacterial diarrhea in previous studies [ 23 27 ].
Fig.
…”
Section: Resultsmentioning
confidence: 89%
“…Subsequently, 10 miRNAs were selected to construct the circRNA-miRNA interaction network (Fig. 4 c), among which 5 were targeted miRNAs of the key candidate circRNA found in this study, and the other 5 selected miRNAs were found to be related to bacterial diarrhea in previous studies [ 23 27 ].
Fig.
…”
Section: Resultsmentioning
confidence: 89%
“…Subsequently, 10 miRNAs were selected to construct the circRNA-miRNA interaction network (Fig. 4c), among which 5 were targeted miRNAs of the key candidate circRNA found in this study, and the other 5 selected miRNAs were found to be related to bacterial diarrhea in previous studies [21][22][23][24][25].…”
Section: Construction Of a Cerna Networkmentioning
confidence: 81%
“…For example, a study showed that mir-423-5p may be an important regulatory molecule for testis development and fertilization [ 56 ]. miR-185 was found to promote proliferation of intestinal epithelial cells [ 57 ]. miR-10391 had been reported to regulate the process of swine influenza virus infestation of host cells through ceRNA mechanism [ 58 ].…”
Section: Discussionmentioning
confidence: 99%